ENHANCING OLIVE OIL COMMUNICATION BY BLOCKCHAIN AGRI-FOOD - Davide Maria Consolaro; Domingo Fernández Uclés; Julio Vena Oya (New Medit)
Blockchain technology has emerged as a promising development in the agri-food sector; however, much of society remains unaware of its potential as an additional certification to ensure the authenticity and safety of agri-food products. This study examines the communication of blockchain information related to olive oil on websites to identify the organizational profiles that prioritize this technology and understand the underlying determinants and strategies. Employing fuzzy set Qualitative Comparative Analysis (fsQCA) and drawing from a comprehensive review of the literature on blockchain traceability in the agri-food sector, we identify the key business variables that influence the extent of website communication. Our findings highlight the proactive communication efforts of organizations that cultivate organic olive oils and embrace sustainable cultivation and production practices. This insight can assist the olive oil sector management in gaining a competitive edge and bridging the information gap between consumers and supply chain operators.